Comprehensive Preparation for the English Language Olympiad as Part of Improving the Quality of Language Education in Russia - A. P. Gulov (Дискурс профессиональной коммуникации, 2022)
Modern foreign language education in Russia is riddled with various challenges, ranging from the forced introduction of interactive technologies to complications imposed by the political agenda. The article analyses Olympiad tasks and their peculiarities at different Olympiad stages, considering various competitive projects, both university Olympiad projects and the All-Russian Olympiad of schoolchildren. The author offers some recommendations on better preparation for the regional and final rounds of the All-Russian School Olympiad, which the author trialled while working with groups and individual students from Moscow and which have proven to be successful. The article specifies manuals which can be used for this purpose as well. Empirical material for the study comprises a survey, aimed at students who attended the courses to prepare for the Olympiad to determine their attitudes toward online courses. The suggested system can function in any region of Russia, which will help the development of young talent throughout the country.